Virtual Reality-Enhanced Higher Education for Inclusive, Innovative, and Sustainable Learning - Ridlo, Saiful; Zulfikasari, Sony; Efrilianda, Devi Ajeng; Rodiyah; Tsong, Chau Kien (Jurnal Pendidikan IPA Indonesia, 2026)
This study aims to develop and validate a Virtual Reality (VR)-based laboratory model and examine its effects on student engagement, confidence, perceived conceptual understanding, and short-term cognitive performance in undergraduate science learning. Using a design-based research and development approach with iterative cycles, the VR laboratory was designed following Outcome-Based Education (OBE) principles and validated through expert judgment and classroom implementation. Data were collected using questionnaires, observations, qualitative reflections, and pretest-posttest assessments. The results indicate that the VR laboratory model demonstrates high pedagogical feasibility and is associated with increased student engagement, learning motivation, operational confidence in using immersive technology, and short-term improvements in conceptual understanding. Qualitative findings highlight the benefits of safe simulation, enhanced spatial visualization, and contextualized experiential learning, while usability issues and learner comfort remain practical challenges that require further refinement. At the institutional level, the validated VR laboratory model is positioned as a pilot-ready digital learning infrastructure that has the potential to support inclusive and quality science education (Sustainable Development Goal 4) and foster educational innovation and digital infrastructure development (Sustainable Development Goal 9). However, the findings primarily reflect short-term, context-specific outcomes; therefore, further large-scale, longitudinal studies with controlled comparisons are required to substantiate claims about long-term learning retention, scalability, and systemic SDG impact.